The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.pmedr.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Associations between green area in school neighbourhoods and overweight and obesity among Norwegian adolescents

Abstract: The aim of the present study was to investigate the relationship between green areas and adolescents' body mass index (BMI). This is based on the notion that nature environment is known to have beneficial effects on human health, and that some of the explanation for this is that green areas are especially motivating or suitable as arenas for physical activity. We included 10,527 participants from the Norwegian Youth Study, which was conducted between 2001 and 2004. The participants reported body weight, height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…Sixteen studies, including two cohort studies 10,36 and 14 cross‐sectional studies, 23,27,33,41–43,50,69,70,72–76 investigated the association between proportion of greenspace in a certain area and dichotomous overweight/obesity (Figure 4). Six studies reported statistically significant lower risks of obesity in association with greenspace 10,23,27,33,36,42 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixteen studies, including two cohort studies 10,36 and 14 cross‐sectional studies, 23,27,33,41–43,50,69,70,72–76 investigated the association between proportion of greenspace in a certain area and dichotomous overweight/obesity (Figure 4). Six studies reported statistically significant lower risks of obesity in association with greenspace 10,23,27,33,36,42 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Dempsey et al 41 found a U‐shaped relationship between urban areas greenspace and obesity within a 1.6‐km buffer zone; those living in areas with the lowest and highest shares of greenspace had the highest probabilities of being obese (BMI ≥ 30). However, two studies 43,75 reported counterintuitive associations between greenspace and obesity. Cummins and Fagg 75 found that residing in areas with the highest proportion of greenspace was significantly associated with greater odds of overweight (12%) and obesity (23%) from 2000 to 2003 but not from 2004 to 2007.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, although those on the periphery of the cities might be surrounded by green fields, these spaces may be unsuitable for engaging in physical activity. This explanation draws from Wilhelmsen, Skalleberg, Raanaas, Tveite, and Aamodt (2017) , who find using cross-sectional data from Norway that increased amount of green areas within school environments increased the odds of overweight and obesity in adolescents. They argue that this due to variation in the types of green spaces available to adolescents, with rural areas consisting of croplands, forests and mountains, with urban areas tending to have more facilitated green spaces conducive to physical activity.…”
Section: Discussion: Potential Explanations and Future Extensionsmentioning
confidence: 99%